De novo mutations in DENR disrupt neuronal development and link congenital neurological disorders to faulty mRNA translation re-initiation. - Haas, M; Ngo, L; Li, S; Schleich, S; Qu, Z; Vanyai, H; Cullen, H; Cardona-Alberich, A; Gladwyn-Ng, I; Pagnamenta, A; Taylor, J; Stewart, H; et al. (Elsevier, 2016)
Disruptions to neuronal mRNA translation are hypothesized to underlie human neurodevelopmental syndromes. Notably, the mRNA translation re-initiation factor DENR is a regulator of eukaryotic translation and cell growth, but its mammalian functions are unknown. Here, we report that Denr influences the migration of murine cerebral cortical neurons in vivo with its binding partner Mcts1, whereas perturbations to Denr impair the long-term positioning, dendritic arborization, and dendritic spine characteristics of postnatal projection neurons. We characterized de novo missense mutations in DENR (p.C37Y and p.P121L) detected in two unrelated human subjects diagnosed with brain developmental disorder to find that each variant impairs the function of DENR in mRNA translation re-initiation and disrupts the migration and terminal branching of cortical neurons in different ways. Thus, our findings link human brain disorders to impaired mRNA translation re-initiation through perturbations in DENR (OMIM: 604550) function in neurons.